MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA MENGGUNAKAN PENDEKATAN SAINTIFIK SISWA KELAS V SD SABILINA TEMBUNG - Mira Andriyani; Fauziyah Harahap; Ramlan Silaban (JURNAL TEMATIK, 2018)
This study aims to improve the activity and student learning outcomes in science lessons class V Sd Private Sabilina Tembung Scientific approach. This research is action research (PTK). The samples in this study were 40 third-grade students for every cycle I and II. The results of the data analysis proved that an increase in activity and student learning outcomes. An increase in activity and student learning outcomes very well. The percentage gain scores for student activities at the beginning of the test trials was 30.00%. later in Cycle I obtained an average percentage score of 68.49%, for the results obtained in Cycle I study an average percentage of 82.50% completeness. later in Cycle II obtained an average percentage of 91.68% of student activity, and to learn the results obtained by an average of 92.65% completeness. Based on observations of the activities of teachers, students, teachers opinion, student responses and student learning outcomes that include classical mastery and purpose, then the Application of Scientific could be declared effective approach to teaching science.